Combined newborn screening allows comprehensive identification also of attenuated phenotypes for methylmalonic acidurias and homocystinuria - Schnabel-Besson, Elena; Kölker, Stefan; Gleich, Florian; Feyh, Patrik; Hörster, Friederike; Haas, Dorothea; Fang-Hoffmann, Junmin; Morath, Marina; Gramer, Gwendolyn; Röschinger, Wulf; Garbade, Sven; Hoffmann, Georg F.; et al. (Nutrients, 2023)
Newborn screening (NBS) programs are effective measures of secondary prevention and have been successively extended. We aimed to evaluate NBS for methylmalonic acidurias, propionic acidemia, homocystinuria, remethylation disorders and neonatal vitamin B12 deficiency, and report on the identification of cofactor-responsive disease variants. This evaluation of the previously established combined multiple-tier NBS algorithm is part of the prospective pilot study “NGS2025” from August 2016 to September 2022. In 548,707 newborns, the combined algorithm was applied and led to positive NBS results in 458 of them. Overall, 166 newborns (prevalence 1: 3305) were confirmed (positive predictive value: 0.36); specifically, methylmalonic acidurias (N = 5), propionic acidemia (N = 4), remethylation disorders (N = 4), cystathionine beta-synthase (CBS) deficiency (N = 1) and neonatal vitamin B12 deficiency (N = 153). The majority of the identified newborns were asymptomatic at the time of the first NBS report (total: 161/166, inherited metabolic diseases: 9/14, vitamin B12 deficiency: 153/153). Three individuals were cofactor-responsive (methylmalonic acidurias: 2, CBS deficiency: 1), and could be treated by vitamin B12, vitamin B6 respectively, only. In conclusion, the combined NBS algorithm is technically feasible, allows the identification of attenuated and severe disease courses and can be considered to be evaluated for inclusion in national NBS panels.
Veröffentlicht: 28. Juli 2023
Gesehen am 27.09.2023